2006
DOI: 10.1111/j.1460-9568.2006.05037.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered PPARγ expression and activation after transient focal ischemia in rats

Abstract: Stroke is a devastating disease with limited treatment options. Recently, we found that the peroxisome proliferator-activated receptor-gamma (PPARgamma) agonists troglitazone and pioglitazone reduce injury and inflammation in a rat model of transient cerebral ischemia. The mechanism of this protection is unclear, as these agents can act through PPAR-gamma activation or through PPAR-gamma-independent mechanisms. Therefore, we examined PPAR-gamma expression, DNA binding and transcriptional activity following str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 61 publications
18
117
1
Order By: Relevance
“…[4][5][6]27 MPO activity and levels of TNFa and IL-1b were significantly increased in the spinal cord tissue of injured rats compared with sham-operated animals 24 h after injury in the present study. In a finding similar to other studies, [17][18][19][20]24 rosiglitazone treatment significantly reduced these increased levels of MPO, TNFa and IL-1b in the present study, thus protecting the spinal cord against secondary degeneration caused by inFammation. It is thought that TZDs confer their neuroprotective effects via the prevention of both microglial activation and inFammatory cytokine/chemokine expression, 28 in concurrence with the findings of the present study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[4][5][6]27 MPO activity and levels of TNFa and IL-1b were significantly increased in the spinal cord tissue of injured rats compared with sham-operated animals 24 h after injury in the present study. In a finding similar to other studies, [17][18][19][20]24 rosiglitazone treatment significantly reduced these increased levels of MPO, TNFa and IL-1b in the present study, thus protecting the spinal cord against secondary degeneration caused by inFammation. It is thought that TZDs confer their neuroprotective effects via the prevention of both microglial activation and inFammatory cytokine/chemokine expression, 28 in concurrence with the findings of the present study.…”
Section: Discussionsupporting
confidence: 79%
“…15,16 The anti-inflammatory and antioxidant properties of rosiglitazone have been studied in models of central nervous system injury and disease, including amyotrophic lateral sclerosis, 17 Parkinson's disease 18 and cerebral ischaemia or haemorrhage. 19 Rosiglitazone has also been shown to prevent apoptosis in experimental traumatic brain injury. 20 The aim of the present study was to investigate the neuroprotective effects of rosiglitazone in a rat SCI model.…”
Section: Introductionmentioning
confidence: 99%
“…172 Cerebral ischemia increases PPAR␥ expression in neurons and microglia, but at the same time DNA binding of PPAR␥ is reduced. 174 DNA binding is restored by PPAR␥ ligands, 170,174,175 and these agents have been shown to reduce ischemic injury in rodent stroke models. 176 Treatment with PPAR␥ ligands reduces microglia and macrophage activation and migration to the periinfarct regions, 177,178 attenuates the expression of ICAM-1, MMP-9, IL-1␤, COX-2, TNF␣, and iNOS, and suppresses production of reactive oxygen species.…”
Section: Ppar␥mentioning
confidence: 99%
“…Several animal studies have demonstrated the beneficial effects of TZDs in improving post-ischemic functional outcome. After focal ischemia, PPAR-gamma expression was observed to be increased in the brain, especially in the peri-infarct area, but surprisingly, its DNA-binding activity was reported to be reduced (15,37). Also, PPAR-gamma agonists trans-repress the transcription of downstream pro-inflammatory genes after ischemia (37) (Table 3).…”
Section: Ppar-gamma and Focal Cerebral Ischemiamentioning
confidence: 99%